Musculocutaneous nerve injury in a collegiate baseball pitcher - Vineyard, A. P.; Gallucci, A.; Imbus, S.; Garrison, J. C.; Conway, J. E. (Journal of Athletic Training, 2019)
Background: A 23-year-old Division 1 NCAA collegiate baseball pitcher presented with vague anterior arm pain following a pre-season game. The athlete described the pain as an "intense stretch" of his right arm that occurred during his last pitch. Initial evaluation revealed tenderness over the right distal bicep. Range of motion assessments of the shoulder and elbow were within normal limits bilaterally. Diminished bicep strength was noted (4/5 with manual muscle break testing). All shoulder and elbow orthopedic tests to rule out various conditions including shoulder impingement, labral pathologies, and instability were unremarkable. A follow-up examination was performed the following day identifying marketable decreased sensation along the athlete`s right lateral antebrachial cutaneous nerve distribution. Therefore, an electromyography (EMG) test was conducted which confirmed a right upper and mid-brachial plexus stretch injury with primary involvement of the musculocutaneous nerve. Differential Diagnosis: Traction injury of the musculocutaneous nerve, second-degree strain of the bicep musculature, or thoracic outlet syndrome involvement. Treatment: The athlete was initially treated with an oral steroid and removed from all throwing activities. The athlete began a comprehensive rehabilitation program that emphasized strengthening the shoulder musculature in an effort to restore bicep musculature strength. However, exercises that caused excessive stress on the biceps such as eccentric focused contractions and exercises involving abduction and extension were avoided to minimize stretching of the musculocutaneous nerve. Additionally, exercises utilizing blood flow restriction (BFR) were introduced on the uninvolved side in an effort to reduce deficits in bicep musculature strength by enhancing hypertrophy factors seen with the use of BFR. This method utilized the idea of the cross-education theory which postulates that strength training of the uninjured extremity results in bilateral strength increases likely through neural adaptation mechanisms specifically with eccentric contractions. A month later, a second EMG study revealed significant reduction of neuropathy findings. However, observed deficits in strength and atrophy of the right bicep musculature continued to be present. Therefore, the athlete was allowed to begin flat-ground throwing activities but was restricted from progressing to mound throwing until this deficit had improved. Rehabilitation continued and inclusion of BFR and progressive resistance exercise of the involved arm were added due to diminished neuropathy findings. The athlete was eventually progressed to mound throwing and returned to full activity three months following initial injury. Uniqueness: Literature regarding musculocutaneous nerve injuries amongst the athletic population is scarce, with only several clinical cases being reported amongst adult and adolescent baseball and softball pitchers. Available documented reports reveal vague initial pain patterns, lack of deficits in range of motion, manual muscle testing, and positive shoulder orthopedic exams with the increased observance of sensory and motor deficits usually occurring several days or weeks following initial injury evaluation. Overstretching of the musculocutaneous nerve may occur in the pitching motion at time of ball release due to the traction force placed through the arm as it attempts to decelerate thus placing excessive stress on the anterior shoulder including increased stress through the bicep musculature.8,9 The amount of shoulder abduction, horizontal abduction, and elbow torque reached prior to ball release has been shown to impact the amount of traction force placed through the arm. Conclusions: Due to vague reports and inconclusive findings upon an initial evaluation of this condition, the initial presentation may be mistaken for other conditions such as biceps brachii strain. Further documentation and literature regarding this condition may be of value to clinicians for awareness and conclusive diagnosis.